1990
DOI: 10.1007/bf00023377
|View full text |Cite
|
Sign up to set email alerts
|

Screening test for deodorizing substances from marine algae and identification of phlorotannins as the effective ingredients in Eisenia bicyclis

Abstract: Aqueous extracts from 33 species of marine algae were assessed for their methyl mercaptan-trapping activity by gas chromatography to search for novel natural oral deodorants. Brown algae belonging to the Laminariales such as Eisenia bicyclis, Ecklonia cava and Ecklonia kurome were found to show remarkable deodorizing action against methyl mercaptan. The effective components in Eisenia bicyclis were identified as a phlorotannin, a group of molecules which are characteristic components of Laminariales. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Other natural substances possessing high deodorizing activities against CH 3SH have been found in some plants, 2 ~ 6) most of them being polyphenols and phenolic derivatives. 3 6) The deodorizing mechanism of polyphenols against CH 3 SH is considered to involve the hydrogen bonds between phenolic hydroxyl groups and the thio! group, an inclusive action, physical association such as adsorption, and an addition reaction, although each has not yet been clarified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other natural substances possessing high deodorizing activities against CH 3SH have been found in some plants, 2 ~ 6) most of them being polyphenols and phenolic derivatives. 3 6) The deodorizing mechanism of polyphenols against CH 3 SH is considered to involve the hydrogen bonds between phenolic hydroxyl groups and the thio! group, an inclusive action, physical association such as adsorption, and an addition reaction, although each has not yet been clarified.…”
mentioning
confidence: 99%
“…group, an inclusive action, physical association such as adsorption, and an addition reaction, although each has not yet been clarified. 6) Figure 1 shows the deodorizing effect of each component of tea catechins such as EGCg, (-)-epicatechin gallate (ECg), (-)-epicatechin (EC) and (-)-epigallocatechin (EGC), and of gallic acid (GA) against CH 3 SH. This assay was performed in a potassium phosphate buffer solution (pH 7.5) at 37°C for 5 min consistent with oral use.…”
mentioning
confidence: 99%
“…Variegatic acid derived from Boletus subvelutipes showed at 2 mmol mL -1 (Negishi et al, 2000). Kita et al (1990) reported inhibitory effect against methyl mercaptan of flavonoid from a terrestrial plant. Urabe et al (1999) also reported inhibitory effect against methyl mercaptan of the extracts from Taraxacum spp., Sonchus asper, Cirsium japonicum, Sasa veitchii, Equisetum arvense,and Houttuynia cordata.…”
Section: Discussionmentioning
confidence: 99%
“…The deodorizing activities of the test compounds against methyl mercaptan were examined using the head space method 8 . The procedure involved 1.0 mL of ethanol or an aqueous solution of the test compound and 1.5 mL of 0.1 M phosphate buffer pH 7 being mixed for 5 sec in a 23-mL test tube, which was then sealed with a silicon cap.…”
Section: Evaluation Of Deodorizing Activitymentioning
confidence: 99%
“…GC analyses were performed using a Shimadzu GC-17A instrument equipped with a packed column 6 m 3 mm i.d., 20 dinonyl phthalates, Uniport HP, 60-80 mesh at 70 ; injector temperature at 120 ; detector temperature at 230 ; carrier gas, nitrogen 40 mL/min; splitless injection; sample injection volume; 5 mL of the head space. Deodorizing activity was calculated from the following equation 8 …”
Section: Evaluation Of Deodorizing Activitymentioning
confidence: 99%